Petlocale: desarrollo de una aplicación móvil para la gestión de la oferta de productos y servicios brindados por veterinarias (2022)
Currently pet owners lack quick access to information on vets. In the event of an emergency affecting the health of a pet or the need for any product or service, the lack of timely information could result in a increase in costs and care time for the animal, which could gradually affect its Health. Therefore, the development of a mobile application called Petlocale is proposed. to facilitate access to veterinary information, thus benefiting both the owners of pets as their companion animals. Kotlin was used for the development of the application. Firebase and Android Studio